Providing global public goods: Electoral delegation and cooperation - Martin G. Kocher; Fangfang Tan; Jing Yu (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
This paper experimentally examines the effect of electoral delegation on providing global public goods shared by several groups. Each group elects a delegate who can freely decide on each group member's contribution (including the contribution of herself) to the global public good. Our results show that people mostly vote for delegates who assign equal contributions for every group member. However, in contrast to standard theoretical predictions, unequal contributions across groups drive cooperation down over time, and it decreases efficiency by almost 50% compared to the benchmark. This pattern is not driven by delegates trying to exploit their fellow group members, as indicated by the theory – quite to the opposite, other-regarding preferences and a re-election incentives guarantee that delegates assign equal contributions for all group members. Since the source of the resulting inefficiency is the polycentric nature of global public goods provision together with other-regarding preferences, we use the term Pinefficiency to describe our finding.
urn:nbn:de:bvb:19-epub-21163-9
Keywords: C92; D72; H41; 330; Global Public Goods; Delegation; Cooperation; Experiment